TRANSFORMATION OF THE ECONOMIC NATURE OF THE BANK IN THE CONDITIONS OF THE DIGITALIZATION: LEGAL ASPECT - Нагайчук, Неля; Басанська, Наталія; Брайченко, Сергій; Чернявський, Анатолій; Фоменко, Валентина (Socio-economic relations in the digital society, 2019)
Banks play a majorrolein the fi nancial business. They are the leading financial intermediaries. Sections of financial services are selected. Th eir legal description is provided. This situation is caused by the predominance of the financial capacity over capacity of other entities of fi nancial intermediation. During the development of economic systems, the role and place of banks in fi nancial intermediation changes that require additional research. It is noted that the development of the banking mediation shall conform to the state of the economy and the market of loan capital. The evolution of organizational forms and forms of ownership of banking business is revealed. Historically, in the framework of the banking business putitsbrokerage business. Mediationis to attract deposits, loans and calculations. Throle of the bank is determined by the type of economy. Systematized scientifi c and methodological approach esto ascertaining the nature of the bank. In domestic scientific literature using three methodological approaches to the interpretation of the term «bank». Оperating approach, which is based on characteristics of the bank as a market institution that provides a set of operations. A comparative approach — based on a comparison of features of banking and other fi nancial institutions; Subject-institutional approach based on consideration of terminological diff erences in the bank as a company, organization or institution Western scholars characterize the bank as an enterprise that engaged in money lending and other transactions; as a financial institution that offers a wide range of services, as an institution that provides a wide range of financial services such as account opening deposits and granting loans and credits. It has been found that in most cases the baset of ormr the concept of «bank» takebasic banking transactions, the only difference among them- from two to fi ve. A similar approach is used as a base and banking law of Ukraine.